Reporting on cash flows: appointment and ways of drawing up (Journal of Economic Research & Business Administration, 2016)
Cash flow – one of the most important aspects of an operational cycle of the organization. Information on cash flow is useful to users of financial statements as she helps them to estimate needs of the company for money and ability to create money and equivalents of money.
Keywords: cash flows; money; report on cash flow; operating activi-ties; investment activity; financial activity.